P993Incidence of atrial fibrillation early after cavotricuspid isthmus ablation. (18th June 2020) - Krisai, P; Streicher, O; Meyre, P; Haemmerle, P; Steiner, F; Reddiess, P; Zeljkovic, I; Pavlovic, N; Ammann, P; Roten, L; Reichlin, T; Madaffari, A; et al.
Abstract: Background: Atrial fibrillation (AF) is a common finding in patients undergoing cavotricuspid isthmus ablation for isthmus dependent right atrial flutter (RAF). Little is known about the time of its occurrence. Purpose: We aimed to investigate the incidence of AF early after RAF ablation in a well-defined, prospective cohort. Methods: A total of 255 participants with RAF ablation from 5 centers and at least one completed follow-up were included. Structured clinical follow-up was performed at 3, 6 and 12 months including a 24 hour Holter-ECG. The endpoint was incidence of AF detected clinically or by Holter-ECG. Risk factors associated with the occurrence of AF were assessed using separate, univariate Cox proportional-hazards models. Results: Mean age was 67 years, 80% were male and previous episodes of AF were known in 40%. Over a mean follow-up of 7.4 (±4.4) months AF was detected in 35 (13.7%) participants after RAF ablation (Figure A). After 3, 6 and 12 months AF was detected in 18 (7.1%), 30 (11.7%) and 34 (13.3%) patients. No difference in the incidence of AF after RAF ablation was found comparing patients with and without a history of AF (log-rank p value = 0.44) (Figure B). Comparing patients with and without AF during follow-up, there was no difference in age (68 vs 66 years, p = 0.36), sex (69 vs 81% male, p = 0.08), prior heart failure (29 vs 19%, p = 0.20), hypertension (43 vs 38%, p = 0.56) or left atrial volume (46.6 vs 39.6 ml, p = 0.10), but patients with previous AF had a lower left ventricular ejection fraction (LVEF) (45.7 vs 52.3%, p = 0.02). In separate, univariate Cox proportional-hazards models only increasing LVEF (Hazard ratio 0.97, 95% confidence interval (0.95; 0.99, p = 0.02)) was associated with a lower risk of incident AF after RAF ablation, but no other risk factor. Conclusions: AF occurred in 13.7% of patients early after cavotricuspid isthmus ablation for RAF. There was no difference in the occurrence of AF between patients with and without previously known episodes of AF. Only impaired LVEF was associated with AF occurrence.